Research methods in sports coaching (Routledge, 2014)
1. Introduction, L. Nelson, R. Groom, P. Potrac Section 1: Philosophical considerations 2. Philosophy of knowledge, C. Mallett, R. Tinning 3. Logical positivism, R. Smith and F. Smoll ' 4. Interpretivism, P. Potrac, R. Jones, L. Nelson 5. Poststructuralism, Z. Avner, L. Jones, J. Denison Section 2: Preparing and initiating the research process 6. Navigating the research process, W. Gilbert, M. Camiré, D. Culver 7. Reviewing the literature, J. Lyle 8. The place of theory, L. Nelson, R. Groom, P. Potrac 9. Writing and representing research, R. Groom, L. Nelson, P. Potrac, B. Smith 10. Ethical considerations, G. McFee Section 3: Quantitative approaches to coaching research 11. Questionnaires, D. Rhind, L. Davis, S. Jowett 12. Systematic observation, G. Morgan, B. Muir, A. Abraham 13. Analysis of quantitative data, A. Midgley, B. Chrismas 14. Judging quantitative research, J. Toner, A. Moran Section 4: Qualitative approaches to coaching research 15. Interviews, L. Purdy 16. Ethnography, C. Cushion 17. Analysis of qualitative data, W. Taylor 18. Judging qualitative research, B. Smith, A. Sparkes, N. Caddick Section 5: Contemporary approaches to coaching research 19. Autoethnography, B. Gearity 20. Discourse analysis, J. Mills, J. Denison 21. Conversation analysis, R. Groom, L. Nelson, P. Potrac, C. Cushion, Section 6: Disseminating coaching research 22. Presenting research, P. Marshall 23. Publishing research, P. Trudel, D. Culver, W. Gilbert